The moderating effect of idiosyncratic risk on the market value of cash: A study of Brazilian family and non-family businesses - Marília Paranaíba Ferreira; Alex Mussoi Ribeiro; Ernesto Fernando Rodrigues Vicente (Revista Contabilidade & Finanças)
ABSTRACT The objective of this research was to test whether idiosyncratic risk affects the market value of cash and whether this value, moderated by such risk, differs between Brazilian family and non-family businesses. Although the family business is the dominant type of organization in the world, the literature highlights the need to explore the behavioral differences between family and non-family businesses. Therefore, this study seeks to fill this gap, by considering that the idiosyncratic risk of the firm is influenced by the more or less conservative behavior of the decision maker. Given the impasse between the risk of expropriation of shareholder wealth by managers through available cash balances and the importance of the immediate availability of cash for the survival of the firm, it is relevant to compare whether an additional Brazilian real (the official currency of Brazil) of retained cash is less valuable for Brazilian family businesses compared to non-family businesses. The research has an impact by providing insights into the value that shareholders attribute to each additional Brazilian real of cash. The empirical model is based on the model developed by Fama and French (1998) and adapted by Dittmar and Mahrt-Smith (2007) and Pinkowitz et al. (2006), and idiosyncratic risk is estimated based on the 3-factor model of Fama and French (1993). The firms were classified as family and non-family using the Reference Form, and a total of 83 firms were analyzed using multiple and quantile regressions. The results show that idiosyncratic risk positively affects the market value of cash and that the market value of cash, moderated by idiosyncratic risk, is lower for family businesses than for non-family businesses. This finding that family control has a different effect on the market value of cash of Brazilian firms when idiosyncratic risk is taken into account contributes to the research in this field.